An Improved Power Management System in Electrosurgery Unit Monopolar Design - Riga Domigata; Tri bowo Indrato; Triana Rahmawati; Narongrit Sanajit (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
In using the Electrosurgery unit, improper power settings and modes can cause tissue damage, so it is necessary to adjust the cutting mode and power settings needed. The purpose of this research is to design power control and cutting mode in Electrosurgery using Arduino nano as a regulator of power and pulse or duty cycle. The contribution of this research is the creation of power control and mode in the Electrosurgery unit to increase power and cutting mode. This is to control the electrosurgery power. The LM2907 IC frequency to voltage circuit is used as a voltage regulator, which is issued according to the frequency with the power selection LOW, MEDIUM, HIGH. The method used is the CMOS 4069 device as a frequency generator at 250 kHz, then the driver pulse is passed and controlled by the ATmega328 IC, then forwarded to an inverter circuit that functions to increase the voltage and output in the form of power. After the measurement process is carried out on the inverter input with a Blend mode three value, the voltage value is obtained at the low setting 100 V error 0.03%, medium setting 110V error 0.02%, High setting 120 V Error -0.02%. While the measurement results in the coagulation mode are the low setting error of 100 V 0.05%, the medium setting error is 110V 0.08%. High setting error is 130 V 0.003%. The measurements show that the error in power management is lower than 1%. The results of this study can be implemented in the electrosurgery unit to reduce tissue damage due to a lack of cutting modes and power management.